Effect of disturbances: voltage sags, voltage unbalance and harmonics in induction motors with squirrel cage rotor (2013)
This paper presents a review of the effects of three electromagnetic disturbances: voltage dips (sags or dips), voltage unbalance and voltage harmonics, on induction motors with squirrel cage. A summary is presented of the most relevant researches related and own research results.